(untitled) (NAU Journal of Technology and Vocational Education, 2025)
The study examined innovation and business acumen in entrepreneurship success in Nigeria. Three research questions were analyzed and three hypotheses were tested. A descriptive research design was used. The population of this study comprised all SMEs in Ogun Central Senatorial District of Ogun State Nigeria who have employees spans between 5-55. A total of 50 SMEs in Abeokuta South Local Government Area Ogun State were selected as sample size using purposive random sampling technique. A self-researcher-designed instrument tagged: Innovation, Business Acumen and Entrepreneurship Success Questionnaire (IBAESQ) was used for data collection with (r = .88). Mean and standard deviation were used for answering research questions. PPMC and regression analysis were used for testing hypotheses. The findings of the study revealed that there was a positive relationship between innovation and entrepreneurial success (r = 0.345, p < .05). Business acumen has a positive impact on entrepreneurial performance (β = .381, t = 4.077, p < .05). There was significant composite contribution of independent variables on the dependent variable; R = 0.74, p < .05. The study recommended that business enterprises should engage more on innovation of their production process to improve their product quality and even enhances good enterprises sustainability.